2002
DOI: 10.1016/s0005-2736(02)00347-4
|View full text |Cite
|
Sign up to set email alerts
|

Programmable chronopotentiometry as a tool for the study of electroporation and resealing of pores in bilayer lipid membranes

Abstract: This paper presents the application of chronopotentiometry in the study of membrane electroporation. Chronopotentiometry with a programmable current intensity was used. The experiments were performed on planar bilayer phosphatidylcholine and cholesterol membranes formed by the Mueller-Rudin method. It was demonstrated that a constant-intensity current flow through the bilayer membranes generated voltage fluctuations during electroporation. These fluctuations (following an increase and decrease in membrane cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…Consistent with the findings of previous studies [1,3,34], generation of I MEP is believed to be stochastic, in that the distribution of membrane lifetimes in GH 3 cells was observed for the same transmembrane voltage. The stochastic origin of I MEP described here apparently is not a result of inhomogeneous distribution in the charging of membrane during externally applied electrical field [5,6], because a relatively homogeneous charging of membrane during large membrane hyperpolarizations was established in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the findings of previous studies [1,3,34], generation of I MEP is believed to be stochastic, in that the distribution of membrane lifetimes in GH 3 cells was observed for the same transmembrane voltage. The stochastic origin of I MEP described here apparently is not a result of inhomogeneous distribution in the charging of membrane during externally applied electrical field [5,6], because a relatively homogeneous charging of membrane during large membrane hyperpolarizations was established in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Membrane electroporation (MEP) is long recognized to exert a drastic increase in the electrical conductivity and permeability of the plasma membrane by applying externally electrical field [1][2][3]. This method has been widely employed in cancer research, gene transfection, drug delivery, and cell fusion [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, this method is appropriate for measuring the resistance of lipid bilayer and the mass flow. It is believed that during these kinds of measurements, the lipid bilayer is more stable due to less voltage stress [27], [30]; therefore, small changes in the membrane structure can also be observed. Scalas et al [31], for example, reported on the time course of voltage fluctuations that followed an increase of the membrane conductance due to the opening and closing of hydrophilic pores [28], [31], [40].…”
mentioning
confidence: 99%
“…Under current-clamp conditions, the transmembrane voltage increases slowly; therefore, stable pores could be formed [27], [29], [32], [41]. The creation of the first pore in the planar lipid bilayer causes a fast reduction in transmembrane voltage, which decreases the probability of next pore creation [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation